In vitro genotoxicity tests point to an unexpected and harmful effect of a Magnolia and Aristolochia association. (4th November 2015) - Nachtergael, Amandine; Poivre, Mélanie; Belayew, Alexandra; Duez, Pierre
Abstract: Ethnopharmacological relevance: in the 1990s, a Belgian cohort of more than 100 patients reported cases of Aristolochic Acid Nephropathy (AAN). This progressive renal and interstitial fibrosis, frequently associated with urothelial malignancies, was consecutive to the Chinese-herbs based slimming capsules intake where a plant Stephania tetrandra S. Moore was replaced by a highly genotoxic Aristolochia species. 70% of the Belgian patients evolved into end-stage renal disease, requiring dialysis or renal transplantation. Furthermore the prevalence of upper urinary tract carcinoma was found alarmingly high in these patients. The Aristolochia adulteration was blamed for the intoxication cases and, to the best of our knowledge, the prescription itself has not been further investigated. Aim of the study: This work proposes to evaluate the in vitro cytotoxicity and genotoxicity of Aristolochia and Magnolia traditional aqueous decoctions and their association. Materials and methods: The cytotoxicity of extracts has been assessed by a MTT cell proliferation assay and the genotoxicity by measuring the presence of γ-H2AX, a phosphorylated histone associated with DNA damages. Results: Treating cells for 24 h with a mixture 1:1 of Magnolia officinalis and Aristolochia baetica decoctions led to an increase in the production of γ-H2AX. Conclusions: This genotoxic potentiation warrants further studies but may lead to an explanatory factor for the "Chinese herb nephropathy" cases. Graphical abstract: